2014
DOI: 10.1017/s0031182014000158
|View full text |Cite
|
Sign up to set email alerts
|

Control options forNeospora caninum– is there anything new or are we going backwards?

Abstract: Recent work has highlighted and enumerated the economic annual losses due to Neospora caninum abortions worldwide, which should provide strong motivation for the control of bovine neosporosis. However, with the recent withdrawal from sale of the only commercially available vaccine, control options for N. caninum have become more restricted. While researchers continue to work on developing alternative efficacious vaccines, what are the control options presently available for the cattle industries? At the practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 167 publications
(255 reference statements)
0
38
0
18
Order By: Relevance
“…Here, the parasite expands asexually to produce a chronic infection harboring infectious cysts that are transmissible to canids. In cattle, it is also efficiently transmitted vertically by transplacental infection, with congenital transmission rates recorded to be 40–95% among calves born to seropositive mothers (Reichel et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Here, the parasite expands asexually to produce a chronic infection harboring infectious cysts that are transmissible to canids. In cattle, it is also efficiently transmitted vertically by transplacental infection, with congenital transmission rates recorded to be 40–95% among calves born to seropositive mothers (Reichel et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…It has been considered that an effective vaccine against neosporosis should either be aimed to prevent infection in uninfected animals, or to prevent abortion or vertical transmission in infected animals (Innes et al, 2002). Previous studies demonstrated that vaccination of naïve cows with live tachyzoites was protective against experimental challenge (Williams et al, 2007;Rojo-Montejo et al, 2013;Weber et al, 2013;Hecker et al, 2013;Reichel et al, 2014;Monney and Hemphill, 2014). The Israeli N. caninum NcIs491 isolate, obtained from brain tissue of an aborted fetus, can be easily grown in culture and is suggested to be of low pathogenicity to laboratory animals including gerbils (Fish et al, 2007) and mice (unpublished results), in comparison with the NC-1 strain (Lindsay et al, 1995;Rettigner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Tachyzoites are transmitted transplacentally to the foetus during pregnancy and may cause abortion. Currently, no economically viable method of controlling the disease has been established [4].…”
mentioning
confidence: 99%